Transplantation of nuclei from 2- to 16-cell embryos into enucleated blastomeres of 2-cell mouse embryos - Landa, V (Folia biologica, 1989)
Individual blastomeres of 2-, 4-, 8- and 16-cell embryos were fused with enucleated blastomeres of 2-cell embryos. The percentage of fused nuclear donor/recipient pairs was high (92 to 100%). Most of the reconstituted embryos cleaved twice within 24 h of in vitro culture and 83% to 95% developed to the morula or blastocyst stage. Increasing the number of blastomeres in reconstituted embryos by the construction of aggregates from blastomeres obtained 24 h after nuclear donor/recipient fusion was effective. All constructed aggregates reached the morula or blastocyst stage within 30 h of in vitro culture. The normal day-13 implantations were recorded after the transfer of reconstituted "half" embryos and aggregates when 8-cell blastomeres were used as nuclear donors.
Keywords: stadium rýhování vajíčka; embryonální a fetální vývoj; Embryo Transfer; kultivační techniky; Blastocyst; Cell Nucleus; morula; Culture Techniques; Nuclear Transfer Techniques; Female; přenos embrya; Blastomeres; fúze buněk; buněčné jádro; zvířata; myši; Mice; blastocysta; Cell Fusion; ženské pohlaví; Morula; Male; techniky jaderného přenosu; blastomery; Embryonic and Fetal Development; Animals; mužské pohlaví; Cleavage Stage, Ovum